HUBUNGAN PENGETAHUAN DAN SIKAP IBU DENGAN KEJADIAN DIARE PADA BALITA DI PUKESMAS SAMATA KECAMATAN SOMBAOPU KABUPATEN GOWA PROPINSI SULAWESI SELATAN - Rusli Taher (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2019)
ABSTRACT Objective: This study aims to determine the relationship of knowledge and attitude of mother with the incidence of diarrhea in infants at Pukesmas Samata Sombaopu District Gowa regency of South Sulawesi Province. Method: The type of this research is Analytical Survey with Cross Sectional Study approach. Where the independent variables (knowledge and attitude) and dependent variable (diarrhea occurrence) with the measurement once and at the same time with the number of samples of 110 people. Results: The results showed that the variables related to diarrhea occurrence were: knowledge variable with indigo p = 0,003 <0,05, and mother attitude variable with p value = 0,003 <0,05. Discussion: Diarrhea is an abnormal or unusual condition of stool expenditure, characterized by increased dilution volume, and frequency more than 3 times daily in children and in infants more than 4 times a day with or without blood mucus (MOH 2010). Conclusion: There is a relationship of knowledge and attitude with diarrhea occurrence. Suggestion: Based on the result of the research, it is hoped that the health staff should do health counseling to the under-five mother about understanding diarrhea, cause diarrhea, diarrhea prevention, and diarrhea management to increase mother's knowledge about diarrhea so as to reduce the incidence of diarrhea in children under five